THE DYNAMICS OF CONSUMPTION BEHAVIOUR: A TIME SERIES ANALYSIS OF INCOME AND PAST CONSUMPTION IN PAKISTAN - ARIF ULLAH, KASHIF RAZA, MUHAMMAD ASIF SHAHZAD; ABDUL MUQEET (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This paper examines the dynamic model of consumption, income and consumer price index in Pakistan based on the time series values between 1985 and 2023. This study has used the Autoregressive Distributed Lag (ARDL) model and impulse response analysis. The ARDL model results demonstrate that income is the most important determinant of consumption in both short and long run. Strong income elasticity of consumption is also confirmed by the fact that a 1 percent increase in income increases consumption by 0.63 and 1.64 in the short and long run respectively. Consumer price index has a weak but insignificant short run effect but positive and significant long run effect on consumption which means that inflation has a time lag effect on consumption behavior. The adverse and substantial error rectification term substantiates the existence of a steady long run equilibrium of the variables and approximately 38% of the imbalance is remedied every period. The impulse response analysis also substantiates these results because it demonstrates that a shock to income has a large and sustained positive impact on consumption, whereas price shocks do not have a large impact on consumption, but instead cause a positive impact that builds up with time. The responses also show that there are two-way interactions between income and consumption implying that there is a feedback mechanism in the economy. All in all, the findings prove that the role of income in the formation of consumption patterns is superior, and the impact of prices is comparatively small and lagged. The results highlight the need to have income-enhancing policies, price stability, and sustainable macroeconomic management to ensure a steady consumption growth and long-run economic stability in Pakistan.